Some Technological and Functional Properties of Lactic Acid Bacteria Isolated from Hardaliye - Muhammet Arıcı; Fatma Coşkun; Gülnaz Çelikyurt; Mustafa Mirik; Mehmet Gülcü; Nazan Tokatlı (Journal of Agricultural Sciences)
Hardaliye is a lactic acid fermented beverage produced from red grape or grape juice with addition of crushed mustard seeds and benzoic acid and can be found in the Thrace region of Turkey. The aims of this study were to determine the dominant species of lactic acid bacteria in hardaliye and to investigate their technological and probiotic properties and potential use as starter culture in the production of Hardaliye. For this aim lactic acid bacteria were isolated from total 28 hardaliye samples (23 hardaliye samples collected from different regions of the Kirklareli in Turkey and 5 hardaliye samples produced with the traditional methods in laboratory conditions) and identified.  After carrying out conventional and molecular biological methods, it was found that all species of lactic acid bacteria belonged to genus Lactobacillus. Lactobacillus plantarum was the dominant species in the microbiota. ~98% of the isolates were similar to each other. Therefore, diversity of effective lactic acid bacteria during the fermentation is very low.  Given the antimicrobial effects and acid production capabilities of lactic acid bacteria, isolates have potential as starter cultures for use in hardaliye production.